Chlorine dioxide treatment decreases respiration and ethylene synthesis in fresh‐cut 'Hami' melon fruit. (22nd July 2013) - Guo, Qin; Lv, Xin; Xu, Fei; Zhang, Yuli; Wang, Jide; Lin, Honghui; Wu, Bin
Summary The effects of chlorine dioxide (ClO2) on respiration and ethylene synthesis of fresh‐cut melon fruit and the possible mechanisms involved were investigated. Fresh‐cut 'Hami' melon fruit fumigated with gas ClO2 in sealed container for 12 h and then stored at 5 °C with 95% relative humidity (RH) for 19 days. Results showed that fruit treated with ClO2 resulted in lower rates of the total respiration, alternative pathway respiration, cytochrome pathway respiration and ethylene production. Furthermore, the expressions of ethylene biosynthesis‐related genes, including CmACS2, CmACO1 and CmACO3 were reduced by ClO2 treatment. Taken together, it is suggested that ClO2 treatment might be an effective way to delay ripening of fresh‐cut 'Hami' melon, partially due to the reduced respiration and ethylene biosynthesis.